DIAGNOSIS OF ENDOCRINE DISEASE: Primary empty sella: a comprehensive review. Issue 6 (December 2017) - Chiloiro, S; Giampietro, A; Bianchi, A; Tartaglione, T; Capobianco, A; Anile, C; De Marinis, L
Abstract : Primary empty sella (PES) is characterized by the herniation of the subarachnoid space within the sella, which is often associated with variable degrees of flattening of the pituitary gland in patients without previous pituitary pathologies. PES pathogenetic mechanisms are not well known but seem to be due to a sellar diaphragm incompetence, associated to the occurrence of upper sellar or pituitary factors, as intracranial hypertension and change of pituitary volume. As PES represents in a majority of cases, a neuroradiological findings without any clinical implication, the occurrence of endocrine, neurological and opthalmological symptoms, due to the above describes anatomical alteration, which delineates from the so called PES syndrome. Headache, irregular menses, overweight/obesity and visual disturbances compose the typical picture of PES syndrome and can be the manifestation of an intracranial hypertension, often associated with PES. Although hyperprolactinemia and growth hormone deficit represent the most common endocrine abnormalities, PES syndrome is characterized by heterogeneity both in clinical manifestation and hormonal alterations and can sometime reach severe extremes, as occurrence of papilledema, cerebrospinal fluid rhinorrhea and worsening of visual acuity. Consequently, a multidisciplinary approach, with the integration of endocrine, neurologic and ophthalmologic expertise, is strongly advocated and recommended for a properly diagnosis, management, treatment and follow-up of PES syndrome and all of the related abnormalities.